β-Catenin Knockdown Affects Mitochondrial Biogenesis and Lipid Metabolism in Breast Cancer Cells - Vergara, Daniele; Stanca, Eleonora; Guerra, Flora; Priore, Paola; Gaballo, Antonio; Franck, Julien; Simeone, Pasquale; Trerotola, Marco; De Domenico, Stefania; Fournier, Isabelle; Bucci, Cecilia; Salzet, Michel; et al. (Frontiers in Physiology, 2017)
β-catenin plays an important role as regulatory hub in several cellular processes including cell adhesion, metabolism, and epithelial mesenchymal transition. This is mainly achieved by its dual role as structural component of cadherin-based adherens junctions, and as a key nuclear effector of the Wnt pathway. For this dual role, different classes of proteins are differentially regulated via β-catenin dependent mechanisms. Here, we applied a liquid chromatography-mass spectrometry (LC-MS/MS) approach to identify proteins modulated after β-catenin knockdown in the breast cancer cell line MCF-7. We used a label free analysis to compare trypsin-digested proteins from CTR (shCTR) and β-catenin knockout cells (shβcat). This led to the identification of 98 differentially expressed proteins, 53 of them were up-regulated and 45 down-regulated. Loss of β-catenin induced morphological changes and a significant modulation of the expression levels of proteins associated with primary metabolic processes. In detail, proteins involved in carbohydrate metabolism and tricarboxylic acid cycle were found to be down-regulated, whereas proteins associated to lipid metabolism were found up-regulated in shβcat compared to shCTR. A loss of mitochondrial mass and membrane potential was also assessed by fluorescent probes in shβcat cells with respect to the controls. These data are consistent with the reduced expression of transcriptional factors regulating mitochondrial biogenesis detected in shβcat cells. β-catenin driven metabolic reprogramming resulted also in a significant modulation of lipogenic enzyme expression and activity. Compared to controls, β-catenin knockout cells showed increased incorporation of [1-14C]acetate and decreased utilization of [U-14C]glucose for fatty acid synthesis. Our data highlight a role of β-catenin in the regulation of metabolism and energy homeostasis in breast cancer cells.